Clinical features and recurrence risk prediction model in patients with idiopathic inflammatory myopathies-associated interstitial lung disease: a retrospective study from Ningbo - Wu, Di; Hou, Yapeng; Fan, Wei; Du, Yingying; Ding, Qunli (Frontiers in Medicine, 2025)
BackgroundIdiopathic inflammatory myopathies (IIMs) are characterized by chronic muscle inflammation and often involve multiple organ systems. Despite treatment, a large number of patients still experience relapse or disease progression. Currently, there is a lack of high-quality studies specifically focusing on recurrence, and early identification of patients at high risk of recurrence remains challenging.MethodsThis retrospective study included patients with idiopathic inflammatory myopathy complicated by interstitial lung disease who were hospitalized in the First Affiliated Hospital of Ningbo University from January 2018 to December 2024. All included individuals were followed up for at least 12 months. The diagnosis of idiopathic inflammatory myopathies and interstitial lung disease (ILD) was based on relevant criteria. A wide range of clinical and laboratory data were collected. Significant variables were screened through univariate and multivariate regression analyses, and risk models for predicting recurrence at 1, 2, and 3 years were constructed, with subsequent evaluation of the models’ performance.ResultsAmong the 93 included patients, the recurrence rate was 23.7%, with a median time to recurrence of 38 months. Approximately 26.1% of recurrences were attributed to drug discontinuation or adjustment. Multivariate analysis suggested that positive anti-RO52 antibody, positive anti-PL7 antibody, elevated white blood cell count, elevated ALT, and elevated LDH were positively correlated with the risk of recurrence. The area under the ROC curve (AUC) for recurrence prediction was: 1-year: 1.00 (95% CI: 1.00–1.00), 2-year: 0.91 (95% CI: 0.75–1.08), 3-year: 0.92 (95% CI: 0.78–1.05).ConclusionBased on baseline clinical and laboratory indicators, this study developed a tool with good predictive ability for IIM-ILD recurrence, which can accurately assess individual recurrence risk and assist in early clinical decision-making.Trial registration numberIRB No:2025092RS.